Identification of ter94, Drosophila VCP, as a modulator of polyglutamine-induced neurodegeneration. - Higashiyama, H.; Hirose, F.; Yamaguchi, M.; Inoue, Y.H.; Fujikake, N.; Matsukage, A.; Kakizuka, A. (Cell Death and Differentiation, 2002)
We have successfully generated a Drosophila model of human polyglutamine (polyQ) diseases by the targeted expression of expanded-polyQ (ex-polyQ) in the Drosophila compound eye. The resulting eye degeneration is progressive and ex-polyQ dosage- and ex-polyQ length-dependent. Furthermore, intergenerational changes in repeat length were observed in homozygotes, with concomitant changes in the levels of degeneration. Through genetic screening, using this fly model, we identified loss-of-function mutants of the ter94 gene that encodes the Drosophila homolog of VCP/CDC48, a member of the AAA+ class of the ATPase protein family, as dominant suppressors. The suppressive effects of the ter94 mutants on ex-polyQ-induced neurodegeneration correlated well with the degrees of loss-of-function, but appeared not to result from the inhibition of ex-polyQ aggregate formation. In the ex-polyQ-expressing cells of the late pupa, an upregulation of ter94 expression was observed prior to cell death. Co-expression of ter94 with ex-polyQ severely enhanced eye degeneration. Interestingly, when ter94 was overexpressed in the eye by increasing the transgene copies, severe eye degeneration was induced. Furthermore, genetical studies revealed that ter94 was not involved in grim-, reaper-, hid-, ced4-, or p53-induced cell death pathways. From these observations, we propose that VCP is a novel cell death effector molecule in ex-polyQ-induced neurodegeneration, where the amount of VCP is critical. Control of VCP expression may thus be a potential therapeutic target in ex-polyQ-induced neurodegeneration.